IMPLEMENTASI KOMPONEN MAQASHID SYARIAH TERHADAP KESEJAHTERAAN PADA KARYAWAN YAYASAN NURUL HAYAT SURABAYA - Novita Andriana; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this research is to determine the welfare of employees at the Nurul Hayat Foundation, which is viewed from the perspective of the maqashid sharia, which is about religion, soul, intelligence, generation, and wealth. The research method used is a case study with a descriptive qualitative approach. Qualitative descriptive is researching a group of people, an object, a condition, or something in the present. The purpose of this descriptive research is to make an accurate description of the facts, traits and relationships between events that occur in real life. This study uses the interview process in primary data collection. The interview process was conducted with 7 employees of the Nurul Hayat Foundation. The results of this research are the Nurul Hayat Foundation as a sharia institution that always prioritizes religious values. Nurul Hayat Institution is the welfare of its employees by implementing policies for its employees. Through these policies all employees feel prosperous and fulfilled their needs as measured by the five indicators of maqashid sharia, namely maintaining religion, maintaining the soul, maintaining intelligence, maintaining generation, and maintaining wealth.Keywords: Employment, Employee Welfare, Islamic Welfare, Maqashid ShariaREFERENCES Al-Qur’an Tafsir dan Terjemahannya. 1978. Bandung: Firma Sumatra Bandung Lembaga Penterjemah dan Tafsir Al-Qur’an.Ahmed Raja Ahmed Haj Ali, Kamaruzaman Bin Noordin,  and Meguellati Achour. 2018. The Islamic Approach of Obligations in Mutual Relations between Employee and Employer. International Journal of Ethics and Systems, Vol. 34 Issue: 3, pp.338-351.Duhriah. 2015. Tingkatan-tingkatan Maqashid Al-Syariah: al-Dharruriyyat, al-Hajiyyat dan al-Tahsiniyyat. Jurnal Vol. 01 No. 1 Januari-Juni 2015. Fauzia, Ika Yunia dan Abdul Kadir Riyadi: 2014. Prinsip Dasar Ekonomi Islam Perspektif Maqashid Al-Syariah. Jakarta: Kencana.Hidayat, Muhammad. 2010. An Introduction to The Sharia Economic. Jakarta: Zikrul Hakim. Kementrian Agama Republik Indonesia. 2017. Listiawati, 2012. Prinsip Dasar Ekonomi Islam. Palembang: Rafah Press.Mursi, Abdul Hamid. 1997. Sumber Daya Manusia yang Produktif Pendekatan Al-Qur’an dan Sains. Jakarta: Gema Insani Press.Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI). 2008. Ekonomi Islam. Jakarta: PT. Raja GrafindoWibowo, Arif. 2012. Maqashid Asy Syariah: The Ultimate Objective of Syariah. Islamic Finance.Yin, Robert K. 2009. Studi Kasus: Desain dan Metode. Jakarta: Raja Grafindo Persada.Zadjuli, Suroso Imam. 2008. Prinsip-prinsip Ekonomi Islam. Surabaya: Fakultas Ekonomi Universitas Airlangga.